Sosialisasi Praktik Akuntansi Sederhana Dalam Kehidupan Sehari-hari pada SMA Swasta Islahil Athfal Rumak - Sutriningsih, Sutriningsih; Utami, Luh (CV. Global Cendekia Inti, 2025)
The socialization activity “Simple Accounting Practices in Everyday Life” was carried out with the aim of providing socialization to students of Islahil Athfal Rumak Private Senior High School in West Lombok Regency on the importance of understanding the application of accounting practices in everyday life. This is because these simple accounting practices can help students manage their finances effectively, such as controlling their expenses and income accurately. Additionally, students can create realistic financial plans for both short-term and long-term goals, such as continuing their education to a higher level. This initiative helps students manage their finances effectively. The outreach program was attended by approximately 30 students. It was conducted by lecturers from the School of Economics 45 Mataram. In this socialization, we provided the benefits of introducing simple accounting in daily activities. One application of accounting practices is by controlling the income and expenses from their pocket money to use it according to their needs. Accounting practices can also provide an understanding of simplicity, avoiding consumptive and wasteful behavior.